O futebol brasileiro como ambiente de negócios: uma análise comparativa de clubes no Brasil e na Inglaterra - Fernández, Robert Alvarez (2008)
This research, an exploratory study, had been reaching for the understanding of the football clubs business environment regarding the marketing administration and the diverse strategic possibilities in revenue obtaining. To achieve such target, besides the marketing and strategy bibliographic research and more specifically in the sport marketing area alongside the analisys of secondary data of the sport industry, a comparison with English football clubs was endevoured. In the empiric phase, two Brazilian football clubs and two English clubs were studied in depth; that made possible the usage of multiple case studies methodology approach. At the research end, the efforts made possible to conclude that a limited market view prevails in the Brazilian market leading the football clubs to neglect important revenue sources not olny on their quantitative aspects but regarding the building of a solid relation with the fan and consumer. It is believed that the analysis peformed in this research and the correlations stablished with the financial data presented may bring contributions both to the academic study of sport and to the Brazilian clubs when rethinking their relations with the fan and carry out actions to bring the fans back to the stadiums. It is believed that the analisys performed in this research may contribute both to the advance of the academic research on this industry but also to the Brazilian Football clubs by leading them to rethink their relationship with their fans and bring them back to the stadiums with all the benefits but simply matchday revenue